Exploring Accelerometer Versus Self-Report Sleep Assessment in Youth With Concussion - Berger, Ivona (Glob Pediatr Health, 2017)
This study examines accelerometer-based and self-report assessment of sleep disturbance from a larger prospective cohort of youth 5 to 18 years of age with postconcussive injury. Twenty-one participants with self-reported sleep disturbance were evaluated using accelerometers. Participants completed the Pittsburgh Sleep Quality Index (PSQI) every 48 hours and also measured sleep via accelerometry. Correlations were conducted matching PSQI scores to accelerometry assessment. PSQI scores were significantly correlated only with “average number of awakenings” (r = −0.21; P = .049). Accelerometer-measured mean (standard deviation) sleep efficiency was 79.9% (5.20%), with normal sleep defined as >85%. The mean (standard deviation) PSQI global score was 10.5 (3.78) out of 21, where scores of >5 indicate subjective insomnia. Results suggest the PSQI and accelerometers may be measuring different attributes of sleep. Both may be needed as actual sleep is important but so is perception of good sleep. These findings call for further validity testing of objective sleep assessment measures and commonly used self-report tools.